2018
DOI: 10.5858/arpa.2018-0043-oa
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of the Combined Positive Score for Programmed Death Ligand-1 Expression and the Approval of Pembrolizumab for Treatment of Gastric Cancer

Abstract: - Combined positive score is a robust, reproducible PD-L1 scoring method that predicts response to pembrolizumab in patients with G/GEJ cancer. This novel scoring method supported US Food and Drug Administration approval of pembrolizumab as third-line therapy for G/GEJ cancer and has facilitated investigation in other indications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
335
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 426 publications
(351 citation statements)
references
References 28 publications
5
335
2
9
Order By: Relevance
“…Our study showed similar prognostic role of IC, patients with IC + DLBCL‐NOS by SP263 and SP142 also had worse prognosis and were independent risk factors for DLBCL‐NOS (Figure , Table ), while those with TC + DLBCL‐NOS by SP263 did not. In addition, we also calculated the combined PD‐L1 expression level with the modified CPS algorithm, which was approved by FDA on 22 Sept. 2017 for 22C3 antibody and was proved had better predictive ability than TPS in gastric cancer . In our study, combined PD‐L1 expression showed comparable prognostic significance with TC and IC for both SP263 and SP142 (Table ); moreover, combined PD‐L1 staining was easier to evaluate than TC and IC, so combined PD‐L1 positive by IHC might be a better option and a reliable predictive marker in DLBCL.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Our study showed similar prognostic role of IC, patients with IC + DLBCL‐NOS by SP263 and SP142 also had worse prognosis and were independent risk factors for DLBCL‐NOS (Figure , Table ), while those with TC + DLBCL‐NOS by SP263 did not. In addition, we also calculated the combined PD‐L1 expression level with the modified CPS algorithm, which was approved by FDA on 22 Sept. 2017 for 22C3 antibody and was proved had better predictive ability than TPS in gastric cancer . In our study, combined PD‐L1 expression showed comparable prognostic significance with TC and IC for both SP263 and SP142 (Table ); moreover, combined PD‐L1 staining was easier to evaluate than TC and IC, so combined PD‐L1 positive by IHC might be a better option and a reliable predictive marker in DLBCL.…”
Section: Discussionmentioning
confidence: 64%
“…For TC, only partially or completely membranous staining was considered as PD‐L1 TC + , and TPS (number of positive TCs/ number of all TCs) was estimated; for ICs, predominantly macrophages and lymphocytes (Figure ), membranous and/or cytoplasmic staining were both considered as PD‐L1 IC + , and the percentage of positive ICs/ total tumor tissue cellularity was estimated. Recently, combined positive score (CPS) was approved by FDA in the utilized of 22C3 antibody in gastric and gastroesophageal junction adenocarcinoma . Different from solid tumor, it was hard to distinguish TC from IC in DLBCL.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, Agilent PD‐L1 IHC 22C3 pharmaDx assay is the only FDA approved diagnostic tool in evaluating PD‐L1 expression following its proven efficacy in clinical trials of pembrolizumab as a treatment option for NSCLC . In this meta‐analysis, we demonstrated the methodologic heterogeneity in determining PD‐L1 expression among the included studies.…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, comparison based on TPS scoring did not reveal a difference between expressers and non‐expressers, whereas comparison using the CPS system demonstrated a significant difference with an advantage in ORR for expressors . KEYNOTE‐059 also demonstrated the superior predictability of the CPS scoring system with a cutoff of 1% when compared to TPS . Although the TPS system was first utilized to receive FDA approval for pembrolizumab treatment in NSCLC, these studies highlight that this scoring system may have different predictive abilities than other systems such as CPS .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation